Engaging people with lived experience of dementia in research meetings and events: insights from multiple perspectives - Snowball, Ellen; Aiken, Christine; Norman, Myrna; Hykaway, Wayne; Dempster, Zoe; Itzhak, Inbal; McLellan, Emily; McGilton, Katherine S.; Bethell, Jennifer (Frontiers in Dementia, 2024)
This perspective article describes the experiences of engaging people with lived experience of dementia in research meetings and events from the perspectives of people with lived experience, researchers, trainees, audience members and others. We outline examples of engagement from different events and describe a video project, initiated by people with lived experience, conveying diverse views about becoming integral collaborators in the Canadian Consortium on Neurodegeneration in Aging (CCNA) annual Partners Forum and Science Days. We also report evaluation data from audiences and present a series of tips and strategies for facilitating this engagement, including practical considerations for supporting people with lived experience.